Variation in leaf size and fluctuating asymmetry of mountain birch (Betula pubescens var. pumila) in space and time: implications for global change research - Zverev Vitali; Kozlov Mikhail V. (MDPI, 2025)
Experimental, latitudinal, and historical approaches have been used to explore and/or predict the effects of global change on biota, and each approach has its own advantages and disadvantages. The weaknesses of these individual approaches can, potentially, be avoided by applying them simultaneously, but this is rarely done in global change research. Here, we explored the temporal and spatial variations in the leaf size and fluctuating asymmetry (FA) of mountain birch (Betula pubescens var. pumila) in the Murmansk region of Russia, with the aim of verifying the predictions derived from the responses of these traits to experimental manipulations of abiotic drivers of global change. The examination of herbarium specimens revealed that leaf length increased during the 20th century, whereas the FA in the number of leaf teeth decreased, presumably reflecting an increase in the carbon and nitrogen availability to plants in that century. Along a northward latitudinal gradient, leaf length decreased whereas FA increased, presumably due to the poleward decreases in air temperature. The study site, collection year, and latitude explained a larger part of the leaf length variation in mountain birch relative to the variation in FA. Leaf length is likely a better indicator than FA in studies addressing global environmental change impacts on plant performance.